Implementation of Advertising and Telemarketing to Increase Room Revenue - Dewa Ayu Astari Intan Puspita; I Ketut Astawa; I Ketut Suparta; I Putu Krisna Arta Widana; I Wayan Nurjaya (International Journal of Glocal Tourism, 2022)
Purpose: This study was conducted to determine the application of advertising and telemarketing by a 4-star hotel located in Payangan, Gianyar, Bali, Indonesia and their effect on increasing room revenue. Research methods: Data collection techniques used are observation, interviews and documentation. The data analysis technique used is multiple regression analysis which aims to determine the magnitude of the influence of advertising and telemarketing to increase room revenue of the hotel, and processed with SPSS 25. Advertising carried out is in the form of print advertisements through brochures or flyers, newspapers, and magazines, electronic advertisements through the internet and social media, as well as special advertisements. Findings: Based on the results of SPSS 25 calculations on multiple determination analysis, it is known that the coefficient of determination is 66.6%, which means that the contribution of advertising (X1) and telemarketing (X2) variables is 66.6% to the rise and fall of room income at the hotel. While the remaining 33.4% is influenced by other factors not included in this study. Implication: Partially or simultaneously, the two independent variables have a positive effect on room income.